2020
DOI: 10.1002/dmrr.3405
|View full text |Cite
|
Sign up to set email alerts
|

An increase in inflammation and islet dysfunction is a feature of prediabetes

Abstract: Aims Type 2 diabetes (T2D) is a global health problem that will be diagnosed in almost 300 million people by 2025 according to the World Health Organization. Before being diagnosed with T2D, individuals may have glucose levels above normal but below the diabetic range. This condition is known as prediabetes. Studies showed that people with prediabetes had an increase in several pro‐inflammatory cytokines in their serum and in their fasting glucose levels. The answer remains unclear when inflammation begins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Previous studies have reported increased levels of TNFα in serum samples of individuals with pre-DM [ 34 ]. Additionally, IL-1β is a macrophage-induced immune system modulator that decreases βcell activity and insulin sensitivity [ 35 ]. Overall, these findings suggest that elevated levels of liver enzymes and inflammation lead to the progression of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported increased levels of TNFα in serum samples of individuals with pre-DM [ 34 ]. Additionally, IL-1β is a macrophage-induced immune system modulator that decreases βcell activity and insulin sensitivity [ 35 ]. Overall, these findings suggest that elevated levels of liver enzymes and inflammation lead to the progression of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be difficult to capture the overall effects of diet on health by studying the relationship of single nutrient with diseases. In this context, the dietary inflammatory index (DII) has been proposed to evaluate the inflammatory potential of the overall diet and link diet to inflammation which was a key driver in the progression of prediabetes and IR ( 12 , 13 ). The DII score is obtained from the diet of an individual based on the pro- and anti-inflammatory properties of the overall dietary compositions, namely, macronutrients, micronutrients, and some other dietary constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Upadhyaya et al reported that serum IL-6 levels in impaired fasting glucose group was dramatically higher than normoglycemic group and mildly lower than hyperglycemic group [31] . It has been reported that IL-6 protein expression at sections of pancreas and isolated islets from prediabetes were signi cantly upregulated compared to the normal persons in a recent study, where the prediabetes criteria only included impaired fasting glucose and HbA1c [32] . Here we added indexes of FBG, 2hFBG and HbA1c into the prediabetes criteria to make the evidences more su cient.…”
Section: Discussionmentioning
confidence: 91%